Spy secrets that can save your life : a former CIA officer reveals safety and survival techniques to keep you and your family protected - Hanson, Jason (Security specialist) (New York, New York : Perigee, an imprint of Penguin Random House LLC, 2015)
"When Jason Hanson joined the CIA in 2003, he never imagined that the same tactics he used as a CIA officer for counter intelligence, surveillance, and protecting agency personnel would prove to be essential in every day civilian life. In addition to escaping handcuffs, picking locks, and spotting when someone is telling a lie, he can improvise a self-defense weapon, pack a perfect emergency kit, and disappear off the grid if necessary. He has also honed his 'positive awareness' - a heightened sense of his surroundings that allows him to spot suspicious and potentially dangerous behavior - on the street, in a taxi, at the airport, when dining out, or in any other situation"--provided by publisher.
Survival intelligence -- Situational awareness: the single most important thing I learned in the CIA -- Your spy escape and evasion kit: crucial items and information for surviving disasters both major and minor -- Become an escape artist: how to easily escape rope, handcuffs, zip ties, and duct tape -- The impenetrable home: how to criminal proof your house -- Travel safety: staying safe in planes, taxis, and hotels -- How to run countersurveillance like a pro -- Social engineering secrets -- How to be a human lie detector -- How to disappear without a trace -- The art of survival driving -- Defending yourself: weapons and important self-defense tactics.
"A Perigee Book."
Includes bibliographical references and index.
Keywords: Life skills; Survival; Disasters; Emergency management; Accidents -- Prevention; Accidents -- Prevention; Disasters; Emergency management; Life skills; Survival